Outcomes following intra-amniotic instillation with indigo carmine to diagnose prelabor rupture of membranes in singleton pregnancies: a single center experience. (16th February 2016) - Adekola, Henry; Gill, Navleen; Sakr, Sharif; Hobson, Deslyn; Bryant, David; Abramowicz, Jacques S.; Soto, Eleazar
Abstract: Objective : To evaluate clinical outcomes of women with singleton pregnancies that underwent intra-amniotic dye instillation (amniodye test) following equivocal diagnosis of prelabor rupture of membranes (PROM). Method : Records of 34 pregnant women who underwent amniodye test for equivocal PROM were reviewed. Comparisons of characteristics, amniotic fluid (AF) cultures, AF interleukin (IL)-6 concentrations, and placenta pathology results between women who tested positive and those who tested negative were performed. A sub-analysis of women who were amniodye test-negative was also performed. Results : (1) Commonest indication for amniodye test was a typical history of PROM with positive conventional tests and persistently normal AF volume, (2) amniodye test-positive women had a shorter procedure-to-delivery interval ( p = 0.008), and a greater proportion of histologic acute chorioamnionitis ( p = 0.04) and funisitis ( p = 0.01) than amniodye-negative women, and (3) in addition to similarities to women with amniodye-positive test, amniodye test-negative women who delivered <34 weeks, had a greater proportion of women with risk for preterm birth ( p = 0.04), than their counterparts who delivered between 34 0/7 and 36 6/7 weeks. Conclusion : Equivocal diagnosis of PPROM should warrant an amniodye test to avoid iatrogenic intervention in women with intact amniotic membranes. AF analysis should be performed in amniodye test-negative women.